INTEGRATING CRITICAL THINKING IN TEACHING ACADEMIC WRITING - Dewi Sri Wahyuni (UAD TEFL International Conference)
One of targets issued by UN through SDGs (Sustainable Development Goals) in education is ensuring that all youth and adults have to achieve literacy and numeracy skills through long live education for both men and women. It is due to facts that education does not nationally wide spread among the developing and mostly, the third world countries. In those countries, the citizens whom literacy and numeracy skills are built up well are only them whose motivation in learning is high. Simply, it can be said that literacy awareness of those countries is unsatisfying. Realizing this fact, Indonesian government revises the National Curriculum of 2013 by the year 2017 and puts some important issues in learning process: (1) integrating five characters building; (2) elaborating literacy skills and 21st century skills (4C); and (3) integrating High Order Thinking Skill. Not only applied in lower education, these rules can be adopted also in higher education, such as university. Based on the literacy awareness and 4C skills that have to be developed during learning process, this research is aimed at increasing students’ soft skills through integrated character building, literacy skills habit, and critical thinking awareness in academic writing class. By enrolling action research to gain the objectives and taking whole semester, this research works on increasing students’ autonomy and honesty in learning, literacy in reading through article journal comprehension, and critical thinking through article journal summarizing.